Integrated risk management in the era of ir4.0: leveraging on business model canvas for the “royal malaysian police of the future” - Hasni, Noor Azreen; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
To ensure the need and sustainability of the delivery system, risk management is an important aspect of management in ensuring the continuity of public sector services, particularly the public safety and security sector. For National Public Sector, the Risk Management Master Plan, the policy that is the main reference is the General Circular Letter No. 6 Year 2005: Public Sector Information Security Risk Assessment Guidelines, YAB Prime Minister's Order No.1 of 2009: The Integrity Management System of the Malaysian Government's Management System and the Malaysian Public Sector Management of Information & Communications Technology Security Handbook (MyMIS). Therefore, the Royal Malaysian Police (RMP) formulated and designed the RMP Risk Management Plan (RMPRMP) in line with the department's strategic direction to ensure an efficient, transparent and friendly delivery system. The aim of this paper is to review the risk management in RMP and subsequently making RMP continuously relevance in the digital era. Disruptive forces such as IR4.0 and new business models can pave the way for explosive growth or take down reputable giants. Having a strategy in place to identify, address and harnessing on these emerging and disruptive forces, analyze and prioritize their importance, understand their long-term implications, highlight and plan for action with enterprise risks management is imperative for RMP to thrive in the digital era. This paper will discuss on the business model options of the RMP-of-the-Future by utilizing the business model canvas (BMC) framework, together with its associate new risks and challenges. This BMC may facilitate and help RMP-of-the-Future in identifying the key assets, thus as an enabler for the formulation of an effective enterprise risk management system.